PROTOTIPE ANTENA BI-HORN DENGAN DUA ARAH RADIASI DAN SATU FEEDING MONOPOLE BEROPERASI PADA FREKUENSI 2,4 GHz - Ifa Hidayah; Yono Hadi Pramono (Jurusan Teknik Informatika, 2009)
Prototype of A bi-horn antenna with double sides radiation using monopole feeding in a rectangular waveguide for 2.4 GHz frequency operation has been investigated. Dimension of this device structure is divided into three sections which the whole structure are fabricated from Aluminium plate with 2 mm of thickness . A rectangular Waveguide 12 x 6.1 x 12 cm3 of volume size is embedded between feeding apertures of horn antenna. Both horn antenna structures are similar which each horn having the front aperture about 50x38 cm2 of wide and 57cm of length . The Total length of the whole structure is about 127cm. The monopole Feeding is constructed by a copper bar with 3mm of diameter and 3 cm of length which is soldered on the tail of N-Female Connector. The characteristics of this antenna is measured under Network Analyzer equipment for obtaining their Return Loss, VSWR, Bandwidth, Gain and Radiation Pattern . The results show the Return Loss -17.692 dB is found at a frequency of 2.4 GHz with VSWR=1.3 and The bandwidth 838 MHz for range 2.173 to 2.789 GHz. The Optimum VSWR=1.05 and Return Loss -31.431dB is obtained at frequency 2.549 GHz . Both of Maximum Radiation for 0oand 180o are obtained which having 13dBi Gain for E-Plane and 7dBi Gain for H-Plane. This antenna can be favorable applied to wi-fi communication (aeronet) especially at repeater station between point- to- point access or joining their access point (WDS) by only using one card radio of 2.4GHz for attaining a longer distance.